How Shame Affects Writing - Miller, Taryn Alayna (URJ-UCCS: Undergraduate Research Journal at UCCS, 2015)
Shame has a big effect on our lives, yet no one ever wants to talk about it. Dr. Brene Brown, leading shame researcher, defines shame as the "fear of disconnection" in her book I Thought It Was Just Me. She also discusses how much of shame has to do with our fear of how others perceive us; yet, she does not go into the role shame plays in writing. This study stems from Brown's observations, but it goes deeper by examining how shame affects writers. The responses were mostly taken from college students at UCCS, with a few participants who have already graduated college. These older participants show that shame is universal. This shame manifests when writers have intrusive negative thoughts and feelings while trying to write, including telling themselves they are stupid, bad writers, not good students, etc. This differs from the guilt a student might feel from procrastinating on an assignment or not putting forth his/her best effort. The responses from the survey showed where shame in writing comes from and common coping techniques students use to handle it. Responses varied from the avoidance of writing to needing to take a break from writing when the shame became overpowering.